Whey based beverages - new generation of dairy products - Irena Jeličić; Rajka Božanić; Ljubica Tratnik (Mljekarstvo)
Whey is a by product in the process of cheese production. Composition and characteristics of whey are depending on the production technology, the end product and the quality of used milk. Liquid whey consists of approximately 93% water and contains almost 50% of total solids present in the milk of which lactose is main constituent. Lactose is the main constituent of whey while proteins represent less than 1% of total solids. Minerals and vitamins are present in fewer amounts also. Production of whey based beverages started in 1970's and until today a wide range of different whey based beverages has been developed. They can be produced from native sweet or acid whey, from deproteinised whey, from native whey which was diluted with water, from whey powder or by whey fermentation. Non alcoholic whey beverages include wide range of products obtained by mixing native sweet, diluted or acid whey with different additives like tropical fruits (but also other fruits like apples, pears, strawberries or cranberries), crops and their products (mainly bran), isolates of vegetable proteins, CO2, chocolate, cocoa, vanilla extracts and other aromatizing agents. Special attention is being paid to production of fermented whey beverages with probiotic bacteria where the most important step is the choice of suitable culture of bacteria in order to produce functional beverage with high nutritional value and acceptable sensory characteristics. Non alcoholic whey beverages also include dietetic beverages, drinks with hydrolyzed lactose, milk like drinks and powder drinks. Whey is a very good raw material for production of alcoholic beverages due to the fact that the main constituent of the solid content is lactose (about 70%). Alcoholic whey beverages include drinks with small amount of alcohol (up to 1,5%), whey beer and whey wine. Whey beverages are suitable for wide range of consumers – from children to the elderly ones. They have very high nutritional value and good therapeutic characteristics.